Characteristics of Bolus Using Silicone Rubber with Silica Composites for Electron Beam Radiotherapy - Santi Yuli Astuti; Heri Sutanto; Eko Hidayanto; Gede Wiratma Jaya; Astri Suppa Supratman; Galih Puspa Saraswati (Journal of Physics and Its Applications, 2018)
Bolus is a material that equal with the tissue and functions to increase the dose radiation in surface area in external radiotherapy, which uses electron beam. In this research, bolus was made using silicone rubber (SR) material, which was mixed with silicacomposites material. The bolus with a dimension of 12 x 12 x 0,5 cm3 was successfully made with a various amount of silica composite (2%, 4%, 6%). Bolus was then characterized using linear accelerator (LINAC) with an electron beam for percentage of surface dose (PSD) and using CT-Scan to measurement relative electron density (RED). The energy of electron beam used in this research was5 and 7 MeV. The result shows that RED value increased with increasing the amount of silica composite with higher RED value amounted to 1.186. PSD value increased with increasing the amount of silica composite, higher PSD value of energy in 5 and 7 MeV amounted 106.82% and 106.82% and 100.34%, respectively. The result certified that the silica composite material can increase the percentage of surface dose on electron beam radiotherapy.